Registration of Medicines in the Soviet Control and Licensing System on the Example of the Cardiological Drug Trinitrolong - A. N. Petrenko; P. A. Vasiliev; S. Yu. Martsevich; N. P. Kutishenko; O. I. Zvonareva (Рациональная фармакотерапия в кардиологии)
The article presents the history of the study and registration in the USSR of the buccal form of nitroglycerin (trinitrolong) in the 1970s and 1980s, based on a number of author's publications, documentary evidence and oral stories of participants in clinical trials. The specifics of the passage of the main stages of registration of a new pharmacological agent in the Soviet control and authorization system from the author's idea to the introduction of the drug into clinical practice are described. Some reasons for the lag of the USSR from the countries of the capitalist West in the development and introduction of new cardiac drugs are analyzed.